Redescription of three species of Hysterothylacium (Nematoda: Anisakidae) from marine fishes from the Yellow Sea, China, with the synonymy of Hysterothylacium muraenesoxin (Luo, 1999) - Li, Liang; Xu, Zhen; Zhang, Luping (Zootaxa, 2008)
Three species of Hysterothylacium Ward & Magath, 1917 from the Yellow Sea, China, are redescribed and illustrated by light and scanning electron microscopy. Hysterothylacium fabri (Rudolphi, 1819) collected from Chelidonichthys kumu (Cuvier), Trachurus japonicus (Temminck & Schlegel), Argyrosomus argentatus (Houttuyn), Astroconger myriaster (Brevoort) and Hysterothylacium tasmaniense (Johnston & Mawson, 1945) collected from Lophius litulon (Jordan) are reported for the first time in China. Hysterothylacium amoyense (Hsü, 1933) (originally registered as Contracaecum amoyensis from Amoy, Taiwan Strait, China) is redescribed and compared with Hysterothylacium muraenesoxin (Luo, 1999), concluding that the second species represents a junior synonymy of H. amoyense.